2019
DOI: 10.1080/1369183x.2018.1547019
|View full text |Cite
|
Sign up to set email alerts
|

Beyond breadwinning: Ghanaian transnational fathering in the Netherlands

Abstract: This article probes how gender norms and male migrants' legal and socioeconomic position shape transnational fathering amongst Ghanaian-born fathers, residing in the Netherlands, who have one or more children living in Ghana. Drawing on ethnographic research with Ghanaian transnational fathers, this article compares fathers' attitudes and actual practices. In conformity with cultural expectations of fatherhood in Ghana, the men in this study primarily addressed their paternal role in terms of financial support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…The estrangement reached a point where the migrant had to threaten withholding gifts if Sira continued refusing her calls. Migration can both alienate children from parents (Poeze 2019) and amplify existing tensions in the pre-existing web of care.…”
Section: Re-weaving the Web Of Care: Coping With Parental Migrationmentioning
confidence: 99%
“…The estrangement reached a point where the migrant had to threaten withholding gifts if Sira continued refusing her calls. Migration can both alienate children from parents (Poeze 2019) and amplify existing tensions in the pre-existing web of care.…”
Section: Re-weaving the Web Of Care: Coping With Parental Migrationmentioning
confidence: 99%
“…Similarly, the absence of migrant fathers can result in children feeling estranged despite their fathers' efforts to retain regular communications and the presence of grandparents and/or siblings. Poeze (2019) notes that undocumented Ghanaian fathers, unable to make trips back and forth to Ghana to visit their left behind families, worried about failing to fulfil their social role as fathers. Their predicament dramatises the trade-off between the economic benefits of migrants' remittances aimed at children's improved education and living standards, as opposed to the disbenefits of emotional barriers to spontaneously interacting face-to-face with their children.…”
Section: Transnational Family Care Regimesmentioning
confidence: 99%
“…Brittle borders, surfacing in times of economic crisis and political stress, are illustrated by Bianchera et al's (2019) documentation of the internment of Welsh Italian men during World War II in Great Britain, as well as European Union border controls on the nonnational Asians, Africans and Latin Americans described by Poeze (2019), Martínez-Buján (2019) and Fernandez (2019).…”
Section: Evolving Blurred Brittle and Broken Bordersmentioning
confidence: 99%
“…Studies conducted in African countries (South Africa, Ghana, Nigeria, Kenya, and Cameroon) to investigate their parenting styles and findings indicated that, mothers are the mostly relied as children's caretaker whilst fathers are addressed as bread-winners, whose responsibilities are to provide for their families [9,[25][26][27]. In Baumrind's [13] typologies of parenting, mothers personify both authoritative and permissive style of parenting; adopt a more liberal approach to the upbringing of children whilst, fathers are authoritarian.…”
Section: Theoretical Underpinning and Literature 21 Parenting Stylementioning
confidence: 99%
“…Given that education is a human right; regrettably, women do not always have access to this ultimate right hence reduces their chance to accomplish educational pursuits. In much Africa and Asia women still carry a large liability of the domestic, social, and community development culpabilities [7][8][9]. Women from both continents have been perceived as housekeepers henceforth challenge their education accomplishments.…”
Section: Introductionmentioning
confidence: 99%